Internationalisierung und Kulturtransfer von Marken - Landenberger, Sonia (Comparativ, 2009)
Internationalisation and cultural transfer of brands Everyone knows them – brands which are known all over the world and bring up coherent assignments. But how did such brands develop and become internationally intelligible carriers of meaning working cross-cultural? Within a process of Internationalisation brands received a check of multiple assimilation both to changes in their home- and main-markets and to new forms of communication-channels and -rooms. Thereby the prime markets took wide influence on the definition and direction of this assimilation which was increasingly geared by internationally understood value-based concepts. Coeval transatlantic transfers proceeded that were not only reciprocal and unique but bred another transfer – a re-transfer – on the basis of a transfer that occurred before. Using the example of the Jaguar and Porsche brands it is shown on the basis of a theoretical as well as empirical comparative study how corporate brand strategies and brand communication evolved within the automobile industry.